Polynomial Decay and Computational Numerical Modeling of Timoshenko beam with partial dissipation - Acasiete Quispe, Frank Henry (2018)
We studied the uniform stabilization of a class of Timoshenko systems with partial dissipation of the beam. Our main result is to prove that the semigroup associated to this model has polynomial decay. Moreover, we prove that the semigroup decays polynomially to zero. The system decays polynomially with rate dependingon the coeficients of the problem. We also show the computational modeling of the system showing the results obtained theoretically.